2013
DOI: 10.5539/hes.v3n5p36
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties of Academic Achievement in Principles of Accounting Courses from the Student Perspective: Evidence from Libya

Abstract: Many studies by researchers and accounting educators explore various factors associated with the success or failure of accounting majors in college level accounting courses. This paper identifies and summarizes the main obstacles associated with low student academic achievement in introductory courses in the College of Accounting at Al-Jabal Al-Gharbi University, Libya. The research empirically investigates student perceptions of the difficulties of academic achievement in principles of accounting courses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…Moreover, the results of the study by Addow et al (2013) confirm that English language proficiency correlates positively with academic success. Tailab (2013) confirmed that one of the major obstacles identified was students' lack of English language proficiency. Further, Aidoo-Buameh and Ayagre (2013) concluded a relationship was found between Mathematics at pre-university level and academic performance but found no correlation between pre-university English and academic performance.…”
Section: Choice Of Grade 12 Subjectssupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, the results of the study by Addow et al (2013) confirm that English language proficiency correlates positively with academic success. Tailab (2013) confirmed that one of the major obstacles identified was students' lack of English language proficiency. Further, Aidoo-Buameh and Ayagre (2013) concluded a relationship was found between Mathematics at pre-university level and academic performance but found no correlation between pre-university English and academic performance.…”
Section: Choice Of Grade 12 Subjectssupporting
confidence: 61%
“…The results showed that 'English language proficiency correlates positively with academic success' (Addow et al 2013, 64). Tailab (2013) explored obstacles associated with low student academic achievement in introductory courses in the College of Accounting at a university in Libya. The results indicated that one of the major obstacles was students' lack of English language proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Challenges that relate to the teacher-factors are perceived by less number of students. Meanwhile, only a few identified a challenge with their classmates as well as the class timing.The challenges faced by the students are similar to the factors identified by the previous studies including irrelevant exams (Tailab, 2013) and large class sizes (Araujo, Lima, Oliveira & Miranda, 2015). The personal struggles of the students in the study of accounting were not related to any cited studies herein.…”
Section: Resultssupporting
confidence: 68%
“…The majority of the students admitted the weakness of understanding the basic terminologies in accounting. This also highlighted two noted factors of failure which are English comprehension (Rivero-Menendeza, Urquia-Grandeb, Lopez-Sanchez & Camacho-Minanoa, 2018;Tailab, 2013;Joyce, Hassall, Arquero-Montano & Donosoanes, 2006) and mathematical aptitude (Garkaz, Banimah & Esmaeili, 2011;Shaban, 2015). Read and study the next lessons before coming to class 21.67 18…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation